Magnetic properties and hyperfine interactions of Co1-2xNixMnxFe2O4 nanoparticles. Issue 6 (15th April 2017) - Baykal, A.; Eryiğit, Ş.; Topkaya, R.; Güngüneş, H.; Amir, Md.; Yıldız, A.; Kurtan, U.; Shirsath, Sagar E.
Abstract: Co1-2xNixMnxFe2O4 (0.0≤x≤0.5) nanoparticles (NPs) were prepared via citrate assisted microwave combustion route. XRD analysis confirmed the cubic structure (spinel) of all samples. Average crystallite size of products (obtained from (311) diffraction line) was in the range of 32.9–43.4 nm. The intense peak appearing at around 531 cm −1 in FT-IR was attributed to the formation of a spinel ferrite. Magnetic properties of the products were investigated by room temperature vibrating sample magnetometer and Mössbauer spectroscopy. The magnetic parameters have been found to strongly depend on the Ni and Mn concentrations. The saturation magnetization continuously decreases with the increasing of the concentration (x). We found that Ni0.5 Mn0.5 Fe2 O4 NP has superparamagnetic character at room temperature. This result was also verified by Mössbauer analysis. Scanning electron microscopic analysis revealed the cubic morphology of all products, EDX and elemental mapping analyses confirmed the expected composition of each product.